Effects of Aminoleban on Consciousness level in Patients with Hepatic Encephalopathy Secondary to Chronic Liver Disease - Khan, Ijaz Muhammad; Hameed, Khalid; Ahmad, Sajjad (Journal of Postgraduate Medical Institute, 2011)
The effects of aminoleban a mixture of branched-chain aminoacids was evaluated on the degree of consciouness level in patients with hepatic encephalopathy. Faixcher's formula of high concentration of brached-chain amino acids and low concentration of aromatic amino acids was used (aminoleban), in a dose of one bottle BD at 30 drops per minutes. A total number of eight patients with liver cirrhosis and encephalopathy were evaluated and the degree of consciousness after aminoleban infusion was recorded. It was found to be ineffective in four, effective in two, and slightly effective in two. A large number of patients need to be studied prospectively to see the effects of aminoleban on consciouness level in patients with hepatic encephalopathy secondary to cirrhosis of the liver.